Holocene Bythocytheridae (Ostracoda: Podocopida) from Southwestern Atlantic deep-sea sediments off Brazil. Part 1: tribes Bythocytherini Sars, 1926 and Jonesini Schornikov, 1981 - Cristianini Trescastro Bergue; Marie-Béatrice Forel; Geise de Santana dos Anjos-Zerfass; Simone Nunes Brandão (Nauplius)
ABSTRACT The Bythocytheridae Sars, 1866 is one of the oldest families of cytheroidean Ostracoda, with a fossil record dating back to the Silurian. During the Cenozoic this family became one of the main constituents of the deep-sea ostracod faunas, with some taxa reaching wide geographic distribution. Bythocytherids are, therefore, important for the understanding of evolution and paleobiogeography in marine Ostracoda. The main purpose of this paper is to present a study of the tribes Bythocytherini Sars, 1926 and Jonesini Schornikov, 1981 through the analysis of 47 sediment samples collected from 12 sites in the Rio Grande Rise and adjacent areas. The 11 species herein recorded are attributed to the genera Bythocythere Sars, 1866 (four species), Bythoceratina Hornibrook, 1952 (two species), Retibythere Schornikov, 1981 (two species), Rhombobythere Schornikov, 1982b (two species), and Ruggieriella Colalongo and Pasini, 1980 (one species). The occurrence of the bythocytherid species in the study area seems strongly influenced by the bathymetry, being more abundant in the shallowest site (~1,250 m) and absent beyond 3,000 m water depth.